Lifestyle Risk Factors for Weight Gain in Children with and without Asthma - Megan E. Jensen; Peter G. Gibson; Clare E. Collins; Jodi M. Hilton; Lisa G. Wood (MDPI AG, 2017)
A higher proportion of children with asthma are overweight and obese compared to children without asthma; however, it is unknown whether asthmatic children are at increased risk of weight gain due to modifiable lifestyle factors. Thus, the aim of this cross-sectional study was to compare weight-gain risk factors (sleep, appetite, diet, activity) in an opportunistic sample of children with and without asthma. Non-obese children with (n = 17; age 10.7 (2.4) years) and without asthma (n = 17; age 10.8 (2.3) years), referred for overnight polysomnography, underwent measurement of lung function, plasma appetite hormones, dietary intake and food cravings, activity, and daytime sleepiness. Sleep latency (56.6 (25.5) vs. 40.9 (16.9) min, p = 0.042) and plasma triglycerides (1.0 (0.8, 1.2) vs. 0.7 (0.7, 0.8) mmol/L, p = 0.013) were significantly greater in asthmatic versus non-asthmatic children. No group difference was observed in appetite hormones, dietary intake, or activity levels (p > 0.05). Sleep duration paralleled overall diet quality (r = 0.36, p = 0.04), whilst daytime sleepiness paralleled plasma lipids (r = 0.61, p =0.001) and sedentary time (r = 0.39, p = 0.02). Disturbances in sleep quality and plasma triglycerides were evident in non-obese asthmatic children referred for polysomnography, versus non-asthmatic children. Observed associations between diet quality, sedentary behavior, and metabolic and sleep-related outcomes warrant further investigation, particularly the long-term health implications.